2020
DOI: 10.1007/s00408-020-00374-x
|View full text |Cite
|
Sign up to set email alerts
|

High Occurrence of Thrombo-Embolic Complications During Long-Term Follow-up After Pleural Infections—A Single-Center Experience with 536 Consecutive Patients Over 17 Years

Abstract: Purpose Pleural infections are associated with significant inflammation, long hospitalizations, frequent comorbidities, and are often treated operatively-all of which are consequential risk factors for thrombo-embolic complications. However, their occurrence following the treatment of pleural infection is still unknown. The aim of the study was to ascertain the early and long-term occurrence of thrombo-embolic events in patients treated for pleural infections. Methods The study included all patients that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, notably, due to the limited sample size of only 27 patients with bronchiectasis, this study did not determine a more reliable incidence of postoperative VTE in patients with bronchiectasis. Likewise, Ala-Seppälä et al [ 27 ]analyzed the occurrence of VTE in more than 400 patients undergoing surgical intervention for pleural infections during long-term follow-up and found that the incidence of VTE was 3.8% at three months, 5.0% at one year, 8.8% at three years, and 12.4% at five years. However, the definite number of pleural infections caused by bronchiectasis is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, notably, due to the limited sample size of only 27 patients with bronchiectasis, this study did not determine a more reliable incidence of postoperative VTE in patients with bronchiectasis. Likewise, Ala-Seppälä et al [ 27 ]analyzed the occurrence of VTE in more than 400 patients undergoing surgical intervention for pleural infections during long-term follow-up and found that the incidence of VTE was 3.8% at three months, 5.0% at one year, 8.8% at three years, and 12.4% at five years. However, the definite number of pleural infections caused by bronchiectasis is unknown.…”
Section: Discussionmentioning
confidence: 99%